The Biblical Repertoire in Minor Fourteenth-Century Civil Political Poetry in the Tuscan Area (Altre Modernità, 2025)
Within the fourteenth-century minor political and civil poetry of the Tuscan area, it is evident that the biblical repertoire is one of the elements that unites a large part of the texts pertaining to this genre. The sacred text, with its authoritativeness, provides a solid referent for the expression and corroboration of political ideas. There are authors, such as Antonio Pucci and Franco Sacchetti, who use biblical precepts and situations to demonstrate the truthfulness of what they say in their verses. Then there are other authors, such as Coluccio Salutati and Antonio Loschi, who, instead, use biblical characters by comparing them to one of their contemporaries, such as Gian Galeazzo Visconti. The repertoire of biblical precepts and teachings is re-proposed and re-adapted according to what authors want to express in their lyric, consequently the exile in Sacchetti and Tedaldi becomes a suffering that allows a man to prove his worth, the acceptance of this suffering enables a person to be elevated by God. Pietro dei Faitinelli uses Jeremiah’s laments to express his pain during exile. Through the analysis of representative examples of the use of the biblical repertoire in 14th-century minor political poetry from the Tuscan area, I highlight similarities and differences between texts.
Keywords: 14th century; political and civil poetry; Tuscany; Minor poetry; Middle-Age; Biblical repertoire